2020
DOI: 10.7554/elife.53051
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of a temporal speech cue to a spatial neural code in human auditory cortex

Abstract: In speech, listeners extract continuously-varying spectrotemporal cues from the acoustic signal to perceive discrete phonetic categories. Spectral cues are spatially encoded in the amplitude of responses in phonetically-tuned neural populations in auditory cortex. It remains unknown whether similar neurophysiological mechanisms encode temporal cues like voice-onset time (VOT), which distinguishes sounds like /b/-/p/. We used direct brain recordings in humans to investigate the neural encoding of temporal speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 119 publications
1
14
0
Order By: Relevance
“…We interpreted these findings as revealing a representation of category perception, but not necessarily reflecting categorical perception, per se. We argue that cortical representations contain phonetic category information which is critically relevant for behavioral categorization, but the within-category differences were not lost (Fox et al, 2020;Frye et al, 2007;Toscano et al, 2010). Moreover, the present study showed that representational warping based on phonetic category can be observed without an explicit labelling task, suggesting that top-down effects may not be necessary for eliciting non-linear encoding patterns.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…We interpreted these findings as revealing a representation of category perception, but not necessarily reflecting categorical perception, per se. We argue that cortical representations contain phonetic category information which is critically relevant for behavioral categorization, but the within-category differences were not lost (Fox et al, 2020;Frye et al, 2007;Toscano et al, 2010). Moreover, the present study showed that representational warping based on phonetic category can be observed without an explicit labelling task, suggesting that top-down effects may not be necessary for eliciting non-linear encoding patterns.…”
Section: Discussionmentioning
confidence: 47%
“…It is unclear whether a similar neurophysiological mechanism i.e. subcortical-cortical transformation, can be observed for temporal cues, such as VOT, which distinguishes voicing categories (see Fox et al, 2020 for cortical representation of a VOT continuum). Moreover, these studies have mainly focused on group-level patterning.…”
Section: Introductionmentioning
confidence: 99%
“…This finely organized heterogeneity in responses implies a cortical topography that takes us beyond traditional structure-function mappings for higherorder syntax-semantics (Naidich et al, 2004). This mosaic architecture has been ascribed to sensory cortices, and to the best of our knowledge has not been shown for higher-level processing in associative cortices (Fox et al, 2020;Tsao, 2020). We speculate that such organization may be a foundational principle underpinning human language.…”
Section: Discussionmentioning
confidence: 76%
“…Neuroimaging and neurophysiological studies support the idea that features also play a central role in how auditory cortex represents speech sounds (see Monahan, 2018 for a review). The spectral and temporal characteristics of speech sounds are encoded by different spectro-temporal receptive fields (STRF) in superior temporal gyrus (STG; Fox et al, 2020;Hullett et al, 2016;Mesgarani et al, 2014;Yi et al, 2019). Different populations in STG code distinct phonetic properties of speech sounds (Mesgarani et al, 2014), including voice onset time (VOT; Fox et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The spectral and temporal characteristics of speech sounds are encoded by different spectro-temporal receptive fields (STRF) in superior temporal gyrus (STG; Fox et al, 2020;Hullett et al, 2016;Mesgarani et al, 2014;Yi et al, 2019). Different populations in STG code distinct phonetic properties of speech sounds (Mesgarani et al, 2014), including voice onset time (VOT; Fox et al, 2020). Moreover, Khalighinejad et al (2017) and Mesgarani et al (2014) showed that stops and fricatives are coded by distinct neuronal populations, independent of their voicing status.…”
Section: Introductionmentioning
confidence: 99%